NS4B self-interaction through conserved C-terminal elements is required for the establishment of functional hepatitis C virus replication complexes - Paul, David; Romero-Brey, Inés; Gouttenoire, Jérôme; Stoitsova, Savina; Krijnse-Locker, Jacomine; Moradpour, Darius; Bartenschlager, Ralf (Journal of virology, 2011)
Hepatitis C virus (HCV) is an important human pathogen, persistently infecting more than 170 million individuals worldwide. Studies of the HCV life cycle have become possible with the development of cell culture systems supporting the replication of viral RNA and the production of infectious virus. However, the exact functions of individual proteins, especially of nonstructural protein 4B (NS4B), remain poorly understood. NS4B triggers the formation of specific, vesicular membrane rearrangements, referred to as membranous webs, which have been reported to represent sites of HCV RNA replication. However, the mechanism of vesicle induction is not known. In this study, a panel of 15 mutants carrying substitutions in the highly conserved NS4B C-terminal domain was generated. Five mutations had only a minor effect on replication, but two of them enhanced assembly and release of infectious virus. Ten mutants were replication defective and used for selection of pseudoreversions. Most of the pseudoreversions also localized to the highly conserved NS4B C-terminal domain and were found to restore replication competence upon insertion into the corresponding primary mutant. Importantly, pseudoreversions restoring replication competence also restored heterotypic NS4B self-interaction, which was disrupted by the primary mutation. Finally, electron microscopy analyses of membrane alterations induced by NS4B mutants revealed striking morphological abnormalities, which were restored to wild-type morphology by the corresponding pseudoreversion. These findings demonstrate the important role of the C-terminal domain in NS4B self-interaction and the formation of functional HCV replication complexes.